Health literacy index: A new tool for health literacy assessment - Farzane Delavar; Shahzad Pashaeypoor; Reza Negarandeh (Tehran University of Medical Sciences, 2018)
Health (hygienic) literacy is a cognitive skill and an important and effective issue in the healthcare system that was first proposed in 1974 in an educational panel about health education. Since then, this concept has been discussed by the researchers in various fields of literacy and health, and many definitions have been presented for it. Usually, health literacy is defined as a wide range of knowledge and skills in accessing, appraising, understanding and applying health information (1). The importance of health literacy impact on the health outcomes of the patients has been well recognized and it has an important role in individual's decision-making regarding their health needs (2). Health literacy as a social and cognitive skill has various aspects including accessing, appraising, understanding and applying. The ability to understand the educational content, as one of its aspects, has a significant importance in the patients (3-6). In recent years, health literacy has been recognized as an important skill that patients require for making an appropriate health decisions in difficult situations they encounter. Improving patients' health literacy would cause outcomes such as increasing the patients' potential to make informed decisions, decreasing health-threatening risks, increasing prevention of the diseases, improving patient safety, and improving quality of life and patient care (7-9). To educate people, usually their general literacy would be considered, not their health literacy; while there is a significant difference between general literacy and health literacy. General literacy means having the ability to read and write and having basic skills. In contrast, health literacy is defined as a cognitive and social skill determining the individuals' ability to access, understand, and apply information in order to promote health (10). Studies have shown that limited health literacy is associated with various complications in different aspects of health including lack of access to appropriate health services, less willingness to follow up treatments, less compliance with medication, increased number of visits to the emergency ward, increased duration of hospitalization, and increased mortality rate, and it has a significant effect on using healthcare services (3-6). Furthermore, the negative economic effect of low health literacy on the patients and healthcare system could not be ignored. These issues would indicate the need for paying more attention to individuals' health literacy. According to a study conducted by Montazeri et al in Iran, it has been revealed that half of the Iranian population has a limited health literacy and this limitation is more common in the vulnerable groups such as the elderly, housewives, unemployed people and those with lower education levels; this would put them at more health risks (2). Also, results of various studies have shown that some health information is not appropriate for the audience and would not address their needs; whereas the effect of limited health literacy could be improved using appropriate health information. So, the challenging issue regarding these individuals is how to train them (regarding understanding health information); there are various strategies for resolving this issue such as limiting the information provided at each patient's visit, avoiding technical terms, speaking slowly, finding educational content tailored to individuals' ability to read, using pictures for explaining important concepts, encouraging people for asking more questions and assessing individuals' understanding of the education provided using teach back and show me methods (11). In this regard, in 2011, Centers for Disease Control and Prevention (CDC) designed the Health Literacy Index as a tool for providing appropriate educational content based on people's health literacy. This comprehensive checklist comprises 63 items organized into 10 criteria; its criteria and items are shown in table 1. According to this checklist and based on its ten criteria, the educational process (content, procedure and evidence) would completely be evaluated to limit the effect of health literacy on the understanding of information provided to individuals (12).   Table 1. The criteria of the health literacy index Criterion Items Evaluated subject Plain language 8 Writing style (short and easily readable sentences) Terms (avoiding technical terms) numbers and data (ease in understanding the content) Clear purpose 8 Precision, summaries and reviews Number of key points purpose of material (purposiveness) Using visual elements in the educational content Supporting Graphic 6 Explanatory labels Graphic and images of the educational content in relation with the text to help the understanding of the abstract concepts User involvement 7 Interactive strategies (the level of attention received by the audience and the extent of their active participation through the column of counseling, answer and question, games or competitions and storytelling narrations) Audience response Skill-based learning 3 Focus on behavioral skills (modifying a health behavior and providing examples related to this modification) Audience appropriateness 6 Match between audience and material (cultural and social appropriateness to the audience in terms of their experiences, values and beliefs) Audience identified Instructions 6 User instructions Instructions for using the educational content regarding its technicality, applicability and comprehensiveness Development details 3 Authors' contact information Recent review of the studies Evaluation methods 13 Process, formative and outcome evaluations Strength of evidence 3 Evaluation findings   Andrade and colleagues studied the impact of using this index in providing educational materials for falling in the elderly. The results of this study showed that all the educational information is not suitable for audience and does not meet their needs. However, with the help of Health Literacy Index, it is possible to provide educational materials that are fit for the level of health literacy of elderly (7). Due to the Low health literacy is very common particularly in the elders, it is crucial to provide educational materials that are consistent with the level of health literacy in target groups. Regarding the small number of studies have been conducted on the impacts of using health literacy index, It is imperative that the researchers in the related fields provide empirical evidence for its efficiency and effectiveness.